Influence of phase decomposition on mechanical behavior of an equiatomic CoCuFeMnNi high entropy alloy. (December 2019) - MacDonald, Benjamin E.; Fu, Zhiqiang; Wang, Xin; Li, Zhiming; Chen, Weiping; Zhou, Yizhang; Raabe, Dierk; Schoenung, Julie; Hahn, Horst; Lavernia, Enrique J.
Abstract: Phase decomposition is commonly observed experimentally in single-phase high entropy alloys (HEAs). Hence, it is essential for the consideration of HEAs for structural applications to study and understand the nature of phase decomposition in HEAs, particularly the influence it has on mechanical behavior. This paper describes the phase decomposition in the equiatomic CoCuFeMnNi HEA and how the reported secondary phases influence mechanical behavior. Thermomechanical processing, followed by systematic post deformation annealing treatments, revealed the formation of two distinct secondary phases within the equiatomic face-centered cubic (FCC) matrix phase. Low temperature annealing treatments at 600 °C and below led to the nucleation of Fe-Co rich ordered B2 precipitates that contributed precipitation hardening while sufficiently small in size, on the order of 140 nm in diameter. At temperatures <800 °C Cu segregation, due to its immiscibility with the other constituents, eventually forms a Cu-rich disordered FCC phase that is determined to increase the yield strength of the alloy while reducing the ductility, likely attributable to the presence of additional interfaces. The thermal stability and chemistry of these phases are compared to those predicted on the basis of calculated phase diagram (CALPHAD) analyses. Graphical abstract: Image, graphical abstract